ICT and Active Methodologies to Promote Comprehensive University Education - Marianne Daher; Antonia Rosati; Angie Hernández; Nicole Vásquez; Alemka Tomicic (Universidad Autónoma de Baja California, 2022)
This study reports the results of the implementation of an audiovisual (ICT) device and supporting material in psychology, sociology, and social communication courses in two Chilean universities. A micro-documentary about social programs and their outcomes was produced, and educational capsules containing a section of the microdocumentary together with active learning methodologies were prepared as supporting material. A process and outcome evaluation was conducted, with a mixed-methods methodology and in which a total of 87 students participated. We offer considerations on the implementation of the audiovisual device and active methodologies, and identify the main impacts as a consolidation of theoretical content, a development of professional reflection, and the deployment of interdisciplinary skills. Key aspects involved in using these methodologies to promote student engagement and comprehensive education are discussed.